Book Review: TJ Pempel and Keiichi Tsunekawa (eds.), Two crises, different outcomes: East Asia and global finance - Lee, Pei May (Sage Publishing, 2016)
The Asian Financial Crisis (AFC) ultimately shattered the East Asian economies, while the Global Financial Crisis (GFC) left these economies relatively unscathed. The different implications of the two crises in East Asia have created the rationale for a group of leading experts to compile 10 well-researched chapters into an edited volume by Pempel and Tsunekawa. The book comprises three main parts. The main argument advanced by Pempel in the first part argues that the GFC has had less impact on East Asia compared to the AFC. The second argument believes that East Asian economies are faced with challenges that could obstruct their continued growth.